(3GdCPcGQs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbgGQ GdYRjR GdZaGQ CeG HYO abO bGd Gddg GdYXje GdYRjR GdMcje aGPcQhfi GPcQce s
(3BNQgG (B:s
(3aGLJeY ai gPG GdMOjK Led ef GdahGFO efgG UMI GSfGOg gPG BNQ eG bUOJg ef gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG JUMjMGJs
(3YdjgG ebGHdI Ydi fSNI cJH ai BNQgG GdEeGe GHQGgje Hf YHO GdQMef GdeYQha HGHf GdaQcGM GdOeTbi HNWg Efg bGHdgG Ydi fSNI eYJeOI HNW GdeUfa faSg GdhQbI GdChdi efgG HNW eZGjQ hcPdc ebGOGQ YTQ hQbGJ ai GdOGNd ef hQbI (B21 - 30 s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeYGQa GdYGeIs